1995
DOI: 10.1080/00039896.1995.9955010
|View full text |Cite
|
Sign up to set email alerts
|

Lead, Blood Pressure, and Cardiovascular Disease in Men

Abstract: Animal studies have demonstrated that relatively low doses of lead can produce modest elevations in blood pressure. During the past 10 y, many epidemiologic studies have examined the relationship between low-level lead exposure and blood pressure in humans. These studies were reviewed in a consensus conference, which concluded that the evidence supported the existence of a causal association; however, no formal meta-analysis has been conducted. Epidemiologic studies of blood lead and systolic blood pressure in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
1
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(109 citation statements)
references
References 38 publications
6
97
1
5
Order By: Relevance
“…This may possibly have affected the estimate of the combined association size. A meta-analysis performed by Schwartz J et al 70 in 1995 included 15 studies and showed that a doubling of the blood lead concentration was associated with a significant increase of 1.25 mm Hg in systolic blood pressure, which was 0.25 mm Hg higher than in the present analysis.…”
Section: Discussioncontrasting
confidence: 60%
“…This may possibly have affected the estimate of the combined association size. A meta-analysis performed by Schwartz J et al 70 in 1995 included 15 studies and showed that a doubling of the blood lead concentration was associated with a significant increase of 1.25 mm Hg in systolic blood pressure, which was 0.25 mm Hg higher than in the present analysis.…”
Section: Discussioncontrasting
confidence: 60%
“…Increased blood pressure is probably the most sensitive adverse health effect observed in lead poisoning. Several epidemiological studies have found a significant association between increased blood pressure and body lead burden (31,32). A slight decrease in calcium level was observed, indicating the effect of lead on vitamin D and calcium metabolism (33).…”
Section: Resultsmentioning
confidence: 96%
“…Population research on the cardiovascular effects of Pb has focused largely on the association with blood pressure and hypertension. Meta-analyses of more than 60 researches show strong relationship between systolic and diastolic blood pressure and elevated blood Pb level [22][23][24]. High blood Pb level also correlates cardiovascular mortality and prevalence of peripheral arterial diseases [25][26].…”
Section: Introductionmentioning
confidence: 99%